UPAYA IRAN MENSUKSESKAN PENYELENGGARAAN KTT GNB (KONFRENSI TINGKAT TINGGI GERAKAN NON-BLOK) KE XVI DI TEHERAN GUNA MENINGKATKAN PRESTISE INTERNASIONALNYA TAHUN 2012 - Ardina, Rika; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research porpuse is to description about the efford of Iran tosucceeds Tehran NAM Summit. Iran has got sanction from United States, Security Council of United Nation, and European Union since few years ago. This invites all states in the world to join together for isolating Iran from international forum. Yet, AS and Israelâ€™s threat to forbid all of Non Aligned Movement members to attend the Tehran Summit Iran ignores.This research applying qualitative methods and library research. The author used diplomacy theory with the level of the nation-state analysis the source of the research are from of books, journals, publications, articles, news and internet. Iran succeeds in inviting all of Non Aligned Movement members to come to this agenda. For the first time, the Egyptâ€™s president, after the Camp David Agreement, comes to Tehran for attending this summit. The United Nation secretary, Ban Kimoon, also comes to the agenda.This research, concluded that Iran succeeds in inviting all of Non Aligned Movement members to come to this agenda. The Non Aligned Movement Summit succeeded in making a declaration, which called â€œTehran Declarationâ€. It is a milestone of the existence of the Non Aligned Movementâ€™s role in international affair. Furthermore, the declaration says that the Non Aligned Movement members, including Iran, are permitted to enrich nuclear for international peace.Key Word: sanction, Non Aligned Movement Summit, Iran, US, Security Council of UN, EU, Teheran Declaration.